Climate Change Estimates Surpass Rates Of Climatic Niche Evolution In Primates - Meyer, Andreas; Pie, Marcio (My University, 2022)
Primates might be particularly vulnerable to experiencing adverse effects from climate change, given their level of exposure, sensitivity to climatic conditions, and biological traits associated with extinction proneness (e.g., low dispersal ability). Therefore, a key question is whether primates will be able to adapt fast enough to keep up with future climate change. In this study, we used phylogenetic comparative methods to estimate rates of climatic niche evolution for 293 species of primates. We then compared these with projected rates of future climate change. We show that for temperature-related variables, future rates are in general >2800 times faster than rates of niche evolution characteristic of their recent evolutionary past. For precipitation-related variables, the overall difference between rates is >6700. If emissions continue unabated, differences between past and future rates can be at least 4800-fold for temperature-related variables and >7900-fold for precipitation. Species occurring in Central South America, Central and Eastern Africa, Southeast Asia, and the Malay Archipelago are expected to experience the fastest rates of future climate change, relative to their past rates of climatic niche evolution. Our results suggest that primate adaptation to future climate change would require rates of niche evolution unparalleled in the recent history of the group. These findings reinforce the evidence that climate change is a major threat to primates worldwide.
Keywords: Ancestral character states; Adaptation; Phylogenetic comparative methods